2016
DOI: 10.1007/s00449-016-1656-z
|View full text |Cite
|
Sign up to set email alerts
|

Fermentation of de-oiled algal biomass by Lactobacillus casei for production of lactic acid

Abstract: De-oiled algal biomass (algal cake) generated as waste byproduct during algal biodiesel production is a promising fermentable substrate for co-production of value-added chemicals in biorefinery systems. We explored the ability of Lactobacillus casei 12A to ferment algal cake for co-production of lactic acid. Carbohydrate and amino acid availability were determined to be limiting nutritional requirements for growth and lactic acid production by L. casei. These nutritional requirements were effectively addressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Since natural LAB cannot directly hydrolyze and ferment polysaccharides present in lignocellulose physical and/or chemical and/or enzymatic pre-treatment(s) of biomass are necessary. Several examples of fermentation of different pre-treated/hydrolyzed lignocellulosic feedstocks by LAB have been reported that include de-oiled algal biomass (Overbeck et al 2016), barley bran (Moldes et al 2006), corncob (Guo et al 2010;Bai et al 2016), corn stover (Hu et al 2016;Wang et al 2017), de-oiled cottonseed cake (Grewal and Khare 2018), oak wood chip (Wee and Ryu 2009), paper mill sludge (Marques et al 2008;Shi et al 2015), sugarcane bagasse (Adsul et al 2007;Laopaiboon et al 2010), trimming vine shoots (Bustos et al 2005;Moldes et al 2006), wheat bran (Naveena et al 2005;Li et al 2010), wheat straw (Grewal and Khare 2018) (Table 1).…”
Section: Fermentation Of Pre-treated Lignocellulosic Biomass By Natural Labmentioning
confidence: 99%
See 1 more Smart Citation
“…Since natural LAB cannot directly hydrolyze and ferment polysaccharides present in lignocellulose physical and/or chemical and/or enzymatic pre-treatment(s) of biomass are necessary. Several examples of fermentation of different pre-treated/hydrolyzed lignocellulosic feedstocks by LAB have been reported that include de-oiled algal biomass (Overbeck et al 2016), barley bran (Moldes et al 2006), corncob (Guo et al 2010;Bai et al 2016), corn stover (Hu et al 2016;Wang et al 2017), de-oiled cottonseed cake (Grewal and Khare 2018), oak wood chip (Wee and Ryu 2009), paper mill sludge (Marques et al 2008;Shi et al 2015), sugarcane bagasse (Adsul et al 2007;Laopaiboon et al 2010), trimming vine shoots (Bustos et al 2005;Moldes et al 2006), wheat bran (Naveena et al 2005;Li et al 2010), wheat straw (Grewal and Khare 2018) (Table 1).…”
Section: Fermentation Of Pre-treated Lignocellulosic Biomass By Natural Labmentioning
confidence: 99%
“…These LAB developed the ability to ferment a variety of soluble sugars derived from plant polysaccharide hydrolysis (see next section). Supplementation of cellulases in the growth medium (Adsul et al 2007;° Wee and Ryu 2009;Shi et al 2015;Bai et al 2016;Hu et al 2016;Overbeck et al 2016;Wang et al 2017;Grewal and Khare 2018) or co-cultivation with cellulolytic microorganisms (Shahab et al 2018) have therefore been used as efficient strategies to allow plant biomass fermentation by LAB. Alternatively, the development of recombinant LAB equipped with heterologous cellulase systems has been pursued so as to obtain strains that can directly ferment lignocellulosic feedstocks (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…glucanases from other microbial sources (Moraïs et al, 2014;Okano et al, 2010;Overbeck et al, 2016). Similarly, lactobacilli expressing βglucanases from other sources have been engineered for fermentation or health promoting effects (Liu et al, 2005;Wang et al, 2014a).…”
Section: β-Glucan Metabolic Pathways In Lactobacillusmentioning
confidence: 99%
“…It is worthwhile highlighting some works in which only enzymatic hydrolysis is performed. The fermentation of de-oiled algal cake biomass (Great Salt Lake algal isolate designed USU080) for production of lactic acid is undertaken by Lactobacillus casei [102]. The acid lactic yield is 11.17 g/L by action of three enzymes digested, pepsin, α-amylase and cellulose.…”
Section: Production Of Biosugars and Value-added Products By Chemo-enmentioning
confidence: 99%